Memodelkan Angka Buta Huruf di Provinsi Nusa Tenggara Barat - Anresangsya Pria Satvika; Ni Luh Putu Suciptawati; Made Susilawati (Journal on Education, 2023)
Illiteracy is one of the problems in education in Indonesia. The high illiteracy rate can be an obstacle in the world of education, resulting in a low Human Development Index. West Nusa Tenggara Province is one of the provinces in Indonesia with an illiteracy rate that is still above average with cases reaching 12.58% in 2018. The purpose of this research is to model and obtain factors that significantly affect the illiteracy rate in West Nusa Tenggara Province for the period 2016-2020. The method used in this research is panel data regression. The results obtained in this research show that the best model chosen to modelling the illiteracy rate in West Nusa Tenggara Province is the Fixed Time Effect Model panel data regression with R2 of 73.19%. The independent variables that have a significant effect are the number of poor people, gross regional domestic product (GRDP), primary school student-teacher ratio, and the percentage of households that use computers/laptops.